Alterações comportamentais ocasionadas pela separação mãe-filho durante a hospitalização da criança : um processo de identificação pelo enfermeiro - Farias, Francisca Lucélia Ribeiro de (1985)
The research utilizes the exploratory type of methodology with the objective of identify possible behavioral changes occurred as a consequence of the mother-child separation during the child' hospitalization. The study was developcd from may 1984 to july 1985, in University Pediatric Hospital- -Rio de Janeiro. The statistical test of hypothesis shows that there is a significant diference in the behavior of hospitalizes children when they were away of their mother or substitutes. From there data, the researcher concluded that it is needed tho increment the preparation for psicossocial care of children of member of the health’ and nursing'teams.